Chapter 3. Principles and Practices of Irrigation Management for Vegetables - Peter J. Dittmar; Charles E. Barrett; Lincoln Zotarelli; Michael D. Dukes; Eric H. Simonne (EDIS)
Chapter 3 of the Vegetable Production Handbook.